Effect of purpose-directed acupuncture on the pharyngeal phase in stroke patients with dysphagia based on surface electromyography: a randomized controlled trial - Yan-Qiang Qin; Ying-Chun Sun; Xian-Kuan Cheng; Hai-Jiang Yao; Shao-Hong Li; Zheng-Fan Yang; Tao Zheng; Da-Peng Li; Ling-Yong Xiao (Frontiers in Medicine)
IntroductionDysphagia following a stroke is a common complication that significantly impacts patients’ daily living abilities. Acupuncture has been reported to effectively alleviate post-stroke dysphagia and enhance patients’ quality of life. This study aims to compare the effects of purpose-directed acupuncture (PDA) schemes and conventional acupuncture schemes on post-stroke dysphagia using surface electromyography.MethodsA randomized single-blind controlled study design was employed, where eligible post-stroke dysphagia patients were randomly assigned to the treatment group and control group. Both groups received 4 weeks of treatment based on either PDA or conventional acupuncture in addition to regular dysphagia rehabilitation training. After treatment, patients’ Functional Oral Intake Scale (FOIS) scores, Standardized Swallowing Assessment (SSA) scores, and surface electromyography of swallowing muscles were assessed.ResultsThe study included a total of 58 subjects, with 29 in each treatment group and control group. Compared to the control group, the treatment group showed a significant increase in FOIS scores and a decrease in SSA scores. Surface electromyography results indicated that patients in the treatment group had significantly increased Aemg and Iemg values in the submental muscle group compared to the control group.ConclusionPDA schemes may serve as a more effective treatment approach for post-stroke dysphagia, particularly showing advantages in improving submental muscle strength.Clinical trial registrationThe protocol was registered in the Chinese Clinical Trial Registry (ChiCTR2100053597).